Carbon Nanotube Terahertz Detector - He, Xiaowei; Fujimura, Naoki; Lloyd, J. Meagan; Erickson, Kristopher J; Talin, A. Alec; Zhang, Qi; Gao, Weilu; Jiang, Qijia; Kawano, Yukio; Hauge, Robert H; Léonard, François; Kono, Junichiro (Nano letters, 2014)
Terahertz (THz) technologies are promising for diverse areas such as medicine, bioengineering, astronomy, environmental monitoring, and communications. However, despite decades of worldwide efforts, the THz region of the electromagnetic spectrum still continues to be elusive for solid state technology. Here, we report on the development of a powerless, compact, broadband, flexible, large-area, and polarization-sensitive carbon nanotube THz detector that works at room temperature. The detector is sensitive throughout the entire range of the THz technology gap, with responsivities as high as ∼2.5 V/W and polarization ratios as high as ∼5:1. Complete thermoelectric and opto-thermal characterization together unambiguously reveal the photothermoelectric origin of the THz photosignal, triggered by plasmonic absorption and collective antenna effects, and suggest that judicious design of thermal management and quantum engineering of Seebeck coefficients will lead to further enhancement of device performance.